(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Drainage is one of the most important components of the physical environment that affects agriculture. When we talk about surface water, we mean the flow of a stream regardless of its source. By far, surface water provides significant irrigation that stabilizes and improves agro-economic life in an area that otherwise has rich soil potential. The main objective of this paper is to assess of Drainage Pattern in the Osmanabad district, the present study depends on the secondary data.